Degradation of microbial fluorescence biosignatures by solar ultraviolet radiation on Mars. Issue 2 (April 2014) - Dartnell, Lewis R.; Patel, Manish R.; Cockell, Charles; Burchell, Mark; Martins, Zita
Abstract Recent and proposed robotic missions to Mars are equipped with implements to expose or excavate fresh material from beneath the immediate surface. Once brought into the open, any organic molecules or potential biosignatures of present or past life will be exposed to the unfiltered solar ultraviolet (UV) radiation and face photolytic degradation over short time courses. The key question, then, is what is the window of opportunity for detection of recently exposed samples during robotic operations? Detection of autofluorescence has been proposed as a simple method for surveying or triaging samples for organic molecules. Using a Mars simulation chamber we conduct UV exposures on thin frozen layers of two model microorganisms, the radiation-resistant polyextremophile Deinococcus radiodurans and the cyanobacterium Synechocystis sp. PCC 6803. Excitation–emission matrices (EEMs) are generated of the full fluorescence response to quantify the change in signal of different cellular fluorophores over Martian equivalent time. Fluorescence of Deinococcus cells, protected by a high concentration of carotenoid pigments, was found to be relatively stable over 32 h of Martian UV irradiation, with around 90% of the initial signal remaining. By comparison, fluorescence from protein-bound tryptophan in Synechocystis is much more sensitive to UV photodegradation, declining to 50% after 64 h exposure. The signal most readily degraded by UV irradiation is fluorescence of the photosynthetic pigments – diminished to only 35% after 64 h. This sensitivity may be expected as the biological function of chlorophyll and phycocyanin is to optimize the harvesting of light energy and so they are readily photobleached. A significant increase in a ∼450 nm emission feature is interpreted as accumulation of fluorescent cellular degradation products from photolysis. Accounting for diurnal variation in Martian sunlight, this study calculates that frozen cellular biosignatures would remain detectable by fluorescence for at least several sols; offering a sufficient window for robotic exploration operations.